Tests of the efficiency of steam separators - Whipple, James Halley; Seaton, Roy A. (My University, 1904)
Introduction: Unless steam is passed through a superheater after it leaves the boiler,it will carry with it a certain amount of entrained water. The violent ebulition in the boiler throws more or less water up in the steam space as spray,and some of this is carried along with the steam. Besides this,there is a certain amount of water in the steam caused by condensation in the pipes before it reaches the place where it is to be used. This water increases the initial condensation in the cylinder,and if there is a great deal of it present,may cause the cylinder heads to be blown out. To get rid of,so called "Steam Separators" are used. These depend for their action upon the fact that the water is several hundred times as heavy as the steam,and when the direction of flow of the steam is quickly changed,the inertia of the water carries it on out of the path of the steam into a chamber where it can be drawn off. Ribbed plates called baffles are usually used to collect the water and direct its flow.
Citation: Whipple, James Halley and Seaton, Roy A. Tests of the efficiency of steam separators. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Steam Separators; Efficiency Tests; Condensation; Steam; Theses